Documentary Making for Digital Humanists. - Reid, Darren R. (Open Field Guides Series, 2021)
This fluent and comprehensive field guide responds to increased interest, across the humanities, in the ways in which digital technologies can disrupt and open up new research and pedagogical avenues. It is designed to help scholars and students engage with their subjects using an audio-visual grammar, and to allow readers to efficiently gain the technical and theoretical skills necessary to create and disseminate their own trans-media projects.